1980
DOI: 10.1055/s-2008-1074919
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory and Antipyretic Activities of β-Sitosterol

Abstract: Key Word Index: P-Sitosterol; Anti-inflammatory; Antipyretic. AbstractThe anti-inflammatory and antipyre-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
121
0
6

Year Published

1998
1998
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(129 citation statements)
references
References 2 publications
2
121
0
6
Order By: Relevance
“…The anti-inflammatory activity of BS inhibited the reversed passive Arthus reaction probably because of the inhibition of the mediators that give rise to the full Arthurs lesion; in this sense, other authors have provoked ovoalbumin-induced asthmatic mice, and found that BS mitigated the inflammation by eosinophil infiltration and mucus hypersecretion by goblet hyperplasia, and that various inflammatory biomarkers also decreased in the lung tissue and brochoalveolar lavage fluid (Yuk et Furthermore, our results also showed that BS diminished the edema produced by TPA, as well as the mieloperoxidase activity, results which were related to a non-specific inflammatory reaction. In this respect, studies regarding the anti-inflammatory effect of BS have been published since the early 80s, where authors showed such an effect employing carrageenan-induced edema, cotton pellet implantation and Brewer`s yeast induced pyrexia in rats (Gupta et al, 1980). From that time onward a number of anti-inflammatory, antypiretic, antinociceptive, and immunomodulating activities have also been reported (Bouic, 2002;Saeidnia et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The anti-inflammatory activity of BS inhibited the reversed passive Arthus reaction probably because of the inhibition of the mediators that give rise to the full Arthurs lesion; in this sense, other authors have provoked ovoalbumin-induced asthmatic mice, and found that BS mitigated the inflammation by eosinophil infiltration and mucus hypersecretion by goblet hyperplasia, and that various inflammatory biomarkers also decreased in the lung tissue and brochoalveolar lavage fluid (Yuk et Furthermore, our results also showed that BS diminished the edema produced by TPA, as well as the mieloperoxidase activity, results which were related to a non-specific inflammatory reaction. In this respect, studies regarding the anti-inflammatory effect of BS have been published since the early 80s, where authors showed such an effect employing carrageenan-induced edema, cotton pellet implantation and Brewer`s yeast induced pyrexia in rats (Gupta et al, 1980). From that time onward a number of anti-inflammatory, antypiretic, antinociceptive, and immunomodulating activities have also been reported (Bouic, 2002;Saeidnia et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Beta-sitosterol possessed anti-inflammatory and antipyretic activity (Gupta et al 1980). Methanol extract of rhizome is antidiarrheal (Uddin et al 2006).…”
Section: Indigenous Use (Earlier Studies)mentioning
confidence: 99%
“…It has been demonstrated that the stigmasterol was active in reducing the edema by 41% inhibition at doses of 0.5 mg/ear. 27 Most articles on anti-inflammatory activity describe the most common type of evaluation which are the carrageenan-induced paw edema 26 and the TPA-induced ear edema. 27 However, as several authors describe in the literature, the paw edema test is not specific for anti-inflammatory drugs, as anti-cholinergic drugs also reduce the edema.…”
mentioning
confidence: 99%